Educational practitioners' perceptions of ADHD: a qualitative study of views of the home lives of children with ADHD in the UK. (4th February 2019) - Russell, Abigail Emma; Tay, Marianne; Ford, Tamsin; Russell, Ginny; Moore, Darren
Abstract : There is little research exploring educational practitioners' experiences of working with children with attention deficit/hyperactivity disorder (ADHD). The current study aimed to understand educational practitioners' beliefs concerning the home lives of children with ADHD, and how they perceive that home lives affect children's behaviour in school. Forty‐two practitioners from primary, secondary and pupil referral schools participated in focus groups or interviews. Thematic analysis was used to identify themes arising from the data. Three themes emerged as relevant to beliefs about the home lives of children with ADHD: inconsistency, psychosocial adversity and isolation. Educational practitioners relate their experiences of working with children to what they believe occurs at home. On the basis of these findings, we make recommendations for strategies that school practitioners can use when working with children with ADHD.